Analysis of Factors Affecting The Performance of Elderly Cadres in The Community Health Center - Ahdiny Kadariny; Akhmad Dwi Priyatno; Chairil Zaman; Helen Evelina (Lentera Perawat, 2025)
Life expectancy has only increased by 0.02 per year, with a life expectancy achievement ratio in 2018 of only 86.15%. Several main factors, one of which is the community's ability to obtain health services. This research aims to determine the performance of elderly posyandu cadres in the working area of the Sidorejo Community Health Center, Pagar Alam City in 2024. Type of quantitative research, analytical design with a cross-sectional approach. The population of this study was all elderly posyandu cadres in the working area of the Sidorejo Community Health Center, Pagar Alam City, namely 105 cadres. The sample was calculated using the Slovin technique so that the sample was 105 cadres. Univariate, bivariate data analysis using chi square and multivariate using multiple logistic regression tests. The research results showed that there was a significant relationship between knowledge (p=0.008) attitude (p=0.027) service (p=0.007) and the performance of elderly Posyandu cadres. The independent variables age, gender and education do not have a significant relationship with the performance of elderly Posyandu cadres. The most dominant factor related to the performance of elderly posyandu cadres in the working area of the Sidorejo Health Center, Pagar Alam City in 2024 is the service variable (p = 0.017 OR = 3.295). This research suggests conducting outreach to the community about the importance of using posyandu and providing training or monthly meetings to cadres.